Examination of illustrated story books published between the years of 2004-201for 4-8 age group children in terms of illustration - ABACI, OYA (ELSEVIER SCIENCE BV, 2014)
During the early childhood for the development of the child, picture hooks, or illustrated books, have an important role. Illustrations are an indispendable part of the story and an integral element to the text. The purpose of this study is to examine the illustrated story books published between the years of 2004-2013 for 4-8 age group children in terms of illustration. Screening model was used in this study. The study group was determined by random sampling method; and 50 picture story books in Turkish were selected in this regard. The illustration characteristics of the picture hooks were evaluated by the criteria table prepared taking the expert opinions into account. In general, when picture books enter a child's life, many things are changing. Giving meanings to life, learning concepts, gaining knowledge and experience about life, and acquisition of social rules and manners come into existence. In order for the children who are not yet literate to perceive the story read by adults, they must be supported with visual perception through pictures in addition to auditory perception. Accordingly, preparing visual illustration carefully and according to the developmental characteristics of children by the artists has led to the emergence of more qualified publications on behalf of children's literature. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: Children's literature; illustrated books; visual perception